Pengaruh Cause-Related Marketing terhadap Minat Beli Buku Lekas Sembuh pada Generasi Z di Yogyakarta dan Bandung - Muhammad Hisyam Syafii; Halim Purnomo (Yayasan Literasi Sains Indonesia, 2024)
This study aims to investigate the influence of Cause-Related Marketing (CRM) on the level of consumer buying interest in the book